REFLECTION AS A WAY TO FORM THE LEARNING COMPETENCE OF FUTURE PRE-SCHOOL TEACHERS - Bagdonas, Algimantas; Sauleniene, Sigita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Problem of the research: what reflective technic strategies do the teachers use in their work in order to achieve a quality of teaching and which of them they recommend to their students for learning; what reflections do the students use? Aim of the research: to find out how the students use the reflective methods in the learning process, when improving their learning and what approach to the learning in the long-life perspective is. Objectives of the research: to reason the importance of reflection in the education process. To determine the students’ and teachers’ approach to the usage of reflection in the education process. Methods of research: analysis of documents and scientific literature, content analysis, written survey. The research has shown: The teachers and students positively evaluate the usage of the reflection method in their activity. Reflection is a good device for seeking of education quality. During this process the students overtake the teachers’ experience, develop their competences by getting the consultations. During the consultations the teachers give relevant information about the usage of the most effective learning methods in the study process. The students actively use some of the reflection types, most of which are rarely used. This indicates that in the study process not all the possibilities that could improve the learning process are used.